Predictions for Startups - Ramalakshmi, Eliganti; Reddy Kamidi, Sindhuja (International Journal of Engineering and Technology, 2018)
In general 90 out of 100 startups fail to gain expected funding. There can be several reasons like bad management, lack of sufficient funds, good working team etc. which leads to failure of startup. This work aims to create a machine learning model for predicting the range of funding for the startups based on many key attributesthat are involved at different stages in the startup functioning. It is very important to predict the range of funding prior to the implementation of project and till today not much work is done in this respect. This paper proposes implementing a model to predict the funding of a startups based on many important factors like idea of the startup, place where the startup established, domain vertical to which the startup belongs, prior investors, type of funding the organization is expecting. A model is developed by working on real time data of startups from 2015 to 2017. Classification and regression algorithms are used to build the model.Â Â